Envolvimento da neurotransmissão nitrérgica no hipocampo dorsal no controle da função cardiovascular e das respostas autônomas e comportamentais ao estresse social crônico - Almeida, Jeferson de (Universidade Federal de São Carlos, 2018)
The hippocampus is part of the limbic system, and is directly involved in cognitive processes, anxiety-related defensive behaviors, stress responses, and the neurobiology of depression. Some studies have also reported a role of the hippocampus in the control of cardiovascular function. However, the neurochemical mechanisms involved in the control of behavioral responses and cardiovascular function within the hippocampus are still poorly understood. Nitric oxide (NO) is synthesized from L-arginine by three isoforms of the enzyme nitric oxide synthase (NOS), which are called neuronal (nNOS), endothelial (eNOS) and inducible (iNOS). Thus, one of the hypotheses investigated in the present study was that alterations in the formation of NO from nNOS into the dorsal hippocampus are involved in the cardiovascular and behavioral changes induced by social isolation. A second hypothesis investigated in the present study was that both nNOS, iNOS and eNOS in the dorsal hippocampus are involved in the control of cardiac responses of the baroreflex. We identified that social isolation increased depressive- and anxiety-like behaviors, and the treatment of the dorsal hippocampus with NPLA (selective nNOS inhibitor) or carboxy-PTIO (NO scavenger) reversed the behavioral effect of depressive type. Social isolation did not alter the blood pressure and heart rate increase and the drop in tail skin temperature evoked by restraint stress. However, treatment of the dorsal hippocampus with NPLA increased restraint-evoked pressor and tachycardic responses and decreased tail temperature in isolated, but not control, animals. Social isolation increased levels of nitrotyrosine in the dorsal hippocampus, and a trend of increased nNOS levels was identified. Regarding the cardiac responses of the baroreflex, we observed that treatment of the dorsal hippocampus with carboxy-PTIO decreased the tachycardia to drop in blood pressure. Microinjection of NPLA increased bradycardia to increase in blood pressure, whereas 1400W (selective iNOS inhibitor) decreased reflex tachycardia and increased reflex bradycardia. In addition, administration of L-NAME (non-selective NOS inhibitor) in animals co-treated with NPLA + 1400W (to inhibit nNOS and iNOS) decreased reflex bradycardia. Based on these results, we conclude that nitrergic neurotransmission in the dorsal hippocampus modulates cardiac responses of the baroreflex, and this control is specific to nNOS, iNOS and eNOS. In addition, social isolation increases the release of NO in the dorsal hippocampus, possibly by increasing nNOS expression, and this effect is related to the anxiogenic- and depressive-like behavioral responses evoked by social isolation. Furthermore, this increase in the local formation of NO from nNOS plays an inhibitory role in the increase of arterial pressure and heart rate, in addition to facilitating the sympathetic-mediated vasoconstriction during restraint stress.
Involvement of nitrergic neurotransmission in the dorsal hippocampus in the control of cardiovascular function and autonomic and behavioral responses to chronic social stress
Keywords: nNOS; Óxido nítrico; Estresse de isolamento social; Hipocampo dorsal; Barorreflexo; Nitric oxide; Social isolation stress; Dorsal hippocampus; Baroreflex; CIENCIAS BIOLOGICAS::FISIOLOGIA